Cross-Cultural Conections: Understanding Non-Muslim Students Interest in Arabic - Mukmin, Mukmin; Hidayah, Nurul; Soleha, Ulfa (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
Perception is the way a person views something, this is listed as having an impact on student motivation in following up on this perspective. Arabic language learning is usually the study of Muslim students, but nowadays some Schools open themselves to present opportunities for non-Muslim students to learn Arabic as an additional subject. This study attempts to investigate whether the perception of non-Muslim students can make a positive change in their motivation to learn the language as Muslim students learn it. To bridge this gap, this study explores Non-Muslim students' perceptions towards learning Arabic and its relationship with their motivation to learn it. To answer this gap, this study explored Non-Muslim students' perceptions towards learning Arabic and its relationship with motivation to learn it. To obtain this data, the study was administered to one of the secondary schools that organized Arabic language learning and was attended by 16 non-Muslim students. The results showed that almost all participants had positive perceptions towards learning Arabic. The results also show that Non-Muslim students consider the assignment and interesting packaging of learning presentations to be a motivation in learning. The results of this study can prove that students' perceptions greatly affect learning motivation even though the students are non-Muslim. The results of this study can be useful and enlightening for Arabic language teachers that Arabic language material with good packaging will be accepted by anyone even though this language is very thick with religious studies. إن الإدراك هو الطريقة التي ينظر بها الشخص إلى شيء ما، وهذا مدرج على أنه يؤثر على دافع الطالب في متابعة هذا الإدراك. يكون تعلم اللغة العربية من الطلاب المسلمين، ولكن في الزمن الحاضر تفتح بعض المدارس أبوابها لتقديم فرص للطلاب غير المسلمين لتعلم اللغة العربية كمادة إضافية. وتحاول هذه الدراسة لاستكشاف الامكانات في تعلم اللغة العربية للطلاب غير المسلمين، بالنظر إلى إدراكهم في اللغة العربية و دوافعهم في تعلمهم. وللحصول على هذه البيانات، أُجرى هذا البحث على إحدى المدارس الثانوية و يجري فيها تعليم اللغة العربية، وشارك فيه 16 طالبًا من غير المسلمين. أظهرت النتائج أن جميع المشاركين لديهم إدراكا إيجابيا في تعليم اللغة العربية. كما أظهرت النتائج أيضًا أن الطلاب غير المسلمين يعتبرون أن التدريبات والتقديم الرائع في التعلم يكون دوافع التعلم. يمكن أن تثبت نتائج هذا البحث أن إدراك الطلاب تؤثر كثيرا على دافع التعلم للطلاب غير المسلمين. و هذه النتائج هذه الدراسة أن تكون مفيدة لمعلمي اللغة العربية بأن مادة اللغة العربية ذات المواد الجذابة ستلقى قبولاً من الجميع على الرغم من أن هذه اللغة متعلقة جداً بالدراسات الدينية.